Complex and variable regulation of ΔNp63 and TAp63 by TGFβ has implications for the dynamics of squamous cell epithelial to mesenchymal transition - Pokorná, Zuzana; Tylichová, Zuzana; Vojtesek, Borivoj; Coates, Philip J (Scientific reports, 2024)
TGFβ has roles in inflammation, wound healing, epithelial to mesenchymal transition (EMT), and cancer stem cell states, and acts as a tumor suppressor gene for squamous cell carcinoma (SCC). SCCs are also characterized by high levels of ΔNp63, which induces epithelial cell phenotypes and maintains squamous stem cells. Previous studies indicate a complex interplay between ΔNp63 and TGFβ signaling, with contradictory effects reported. We investigated the effects of TGFβ on p63 isoform proteins and mRNAs in non-malignant squamous and SCC cells, and the role of either canonical or non-canonical TGFβ signaling pathways. TGFβ selectively increased ΔNp63 protein levels in non-malignant keratinocytes in association with SMAD3 activation and was prevented by TGFβ receptor inhibition, indicating activation of canonical TGFβ pathway signaling. TP63 isoform mRNAs showed discordance from protein levels, with an initial increase in both TAP63 and ΔNP63 mRNAs followed by a decrease at later times. These data demonstrate complex and heterogeneous effects of TGFβ in squamous cells that depend on the extent of canonical TGFβ pathway aberrations. The interplay between TGFβ and p63 is likely to influence the magnitude of EMT states in SCC, with clinical implications for tumor progression and response to therapy.
Keywords: Epithelial Cells; transformující růstový faktor beta; Squamous cell carcinoma; Protein Isoforms; TAp63; ΔNp63; Carcinoma, Squamous Cell; lidé; spinocelulární karcinom; epitelové buňky; TGFβ; Transforming Growth Factor beta; protein - isoformy; epitelo-mezenchymální tranzice; Humans; Epithelial-Mesenchymal Transition; EMT